Implementasi Penggunaan Aplikasi Education Management Information System (Emis) di PD Pontren Kementerian Agama Kota Palangka Raya - Sahrul Iman Bhato; Nurul Hikmah; Sirajuddin Noor (Switch : Jurnal Sains dan Teknologi Informasi, 2024)
This study aims to determine the application of the Education Management Information System (EMIS) in Islamic boarding schools that can be utilized in decision making in the Early Education and Islamic Boarding School Section of the Ministry of Religious Affairs of Palangka Raya City. This research is a qualitative research, data collection techniques are done by observation, in-depth interviews, and documentation. This research consists of 4 components, namely the human resource component by measuring internal factors consisting of attitude, skills, and knowledge, where the three benchmarks are sufficiently fulfilled. External factors of human resources with the first indicator of work tools (tools) have not been maximized. Second, work support resources include adequate funds and supporting infrastructure, third, coworkers are quite good in implementation. The minimum hardware requirements are PC/laptop, router, printer, and electricity network. The hardware resource component is still found to be not fully supportive and adequate. The software resource component, in terms of processes and computer programs that support EMIS, is quite well implemented. Data resources in the application of EMIS are seen from 3 sub-indicators, namely data categories, timeliness of data collection, and rules in the data collection process where the three elements are quite well done by EMIS operators. Supporting factors that support the implementation of EMIS consist of first, the role of the leadership by coordinating the implementation of EMIS.